Adding International Business to the Core Program via the Simulation Game - Klein, Ronald D. (Journal of International Business Studies, 1984)
This study reports on the feasibility of adding international business to the business core by using a multinational business simulation game in the capstone policy course. The simulation game is not intended to replace an introductory course or substitute for other approaches. It is intended to provide a minimal introduction where none currently exists and perhaps to aid in overcoming the inertia with regard to relevant curriculum changes that are needed to comply with American Assembly of Collegiate Schools of Business (AACSB) guidelines.